Is consistency the panacea? Inconsistent or consistent tax transfer prices with strategic taxpayer and tax authority behavior - Markus Diller; Johannes Lorenz; Georg Schneider; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2021)
This study investigates how strategic tax transfer pricing of a multinational company (MNC) and two tax authorities in different countries affects production and tax avoidance decisions at the firm level and tax revenues at the country level. We employ a game-theoretical model to analyze the costs and benefits of two tax transfer pricing regimes (consistency vs. inconsistency) under asymmetric information. Though tax transfer pricing harmonization is considered a promising instrument to fight undesired tax avoidance, the implications are largely unclear. We find tax avoidance in equilibrium in both countries under inconsistency. Surprisingly, we identify conditions under which low-tax countries benefit from consistency while high-tax countries benefit from inconsistency. This explains how the strategic interaction of taxpayer and tax authorities under firm-level heterogeneity challenges the implementation of consistent regimes. Understanding the implications of (in)consistent transfer pricing rules is crucial when reforming transfer pricing regulations to fight tax avoidance and double taxation.
Keywords: H20; H26; C72; K34; F53; 330; transfer pricing; transfer pricing inconsistency; tax avoidance; tax harmonization; strategic behavior; real effects